ANALISIS VEGETASI HABITAT NEPENTHES sp. DI HUTAN GAMBUT KAMPUS UNIVERSITAS PALANGKA RAYA, KALIMANTAN TENGAH - Siti Sunariyati; Vinsen Willi Wardhana; Muhammad Rizki (LP4MK STKIP PGRI Lubuklinggau, 2022)
This research is a continuation of previous research on the diversity of pitcher plants (Nepenthes sp) at the University of Palangka Raya. This study aims to determine the habitat characteristics of the pitcher plant (Nepenthes sp) at the University of Palangka Raya. We carried out this research in June-September 2022. The habitat characteristics of pitcher plants were collected by purposive sampling to analyze habitat characteristics data using a quadratic sampling method consisting of two transects with 15 plots based on the findings of Nepenthes sp. at the research site. The first transect is in a secondary forest, and the second transect is in the scrub with slightly open conditions after the fire. The research area was dominated by tree species Cratoxylum glaucum, Acacia mangium, Melaleuca cajuputi, and understorey species dominated by Stenochlaena palustris. A diversity index value is classified as a medium for understorey and saplings and low for poles and trees.